Exploring Tetrathiafulvalene–Carbon Nanodot Conjugates in Charge Transfer Reactions. (29th December 2017) - Ferrer‐Ruiz, Andrés; Scharl, Tobias; Haines, Philipp; Rodríguez‐Pérez, Laura; Cadranel, Alejandro; Herranz, M. Ángeles; Guldi, Dirk M.; Martín, Nazario
Abstract: Carbon nanodots (CNDs) were synthesized using low‐cost and biocompatible starting materials such as citric acid/urea, under microwave irradiation, and constant pressure conditions. The obtained pressure‐synthesized CNDs (pCNDs) were covalently modified with photo‐ and electroactive π‐extended tetrathiafulvalene (exTTF) by means of a two‐step esterification reaction, affording pCND‐exTTF. The electronic interactions between the pCNDs and exTTF were investigated in the ground and excited states. Ultrafast pump–probe experiments assisted in corroborating that charge separation governs the deactivation of photoexcited pCND‐exTTF. These size‐regular structures, as revealed by AFM, are stable electron donor–acceptor conjugates of interest for a better understanding of basic processes such as artificial photosynthesis, catalysis, and photovoltaics, involving readily available fluorescent nanodots.